PENGARUH MATA KULIAH KEWIRAUSAHAAN DAN MOTIVASI DIRI TERHADAP MINAT BERWIRAUSAHA MAHASISWA UNHASY JOMBANG - Wiyadi, Heru; Rochmania, Desty Dwi (Discovery : Jurnal Ilmu Pengetahuan, 2017)
Recently, Hasyim Asy’ary University (Unhasy) Tebuireng Jombang has been activating entrepreneurship education to build entrepreneur mindset for students in accordance with its vision and mission. This research had been done to understand the impacts of entrepreneurship lectures and students’ self-motivation toward entrepreneurship in Hasyim Asy’ari University. This research used ex-post facto research method. The research used quantitative approach, and it will be explained descriptively. It is designed to be descriptive research because it investigates the impact between one variable to other variable; they are variable of entrepreneurship lecture and self-motivation toward variable of entrepreneurship interest. Quantitative approach used in this research because the free variable and bound variable are measured by numbers, then, how much the impact between those two variables will be found. The data were collected by questionnaires. The findings of this research show: (1) entrepreneurship lecture gives the influence of students interest in doing entrepreneurship activities. It can be seen from p-value or significant for entrepreneurship lecture variable (X1) in sig. column is 0.001, which is less than alpha 0.05. While for t value is more than t table, 1.66088 or (1.759 > 1.66088). (2) self-motivation gives student interest in doing entrepreneurship activities. It can be seen from p-value for self-motivation variable (X2) in sig. column is 0.003, which is less than alpha 0.05. While for t value is more than t table of 5% significance level, which t is counted as 1.756, more than t table, 1.66088 or (1.756 > 1.66088). (3) there are significance on impacts of entrepreneurship lecture and self-motivation that simultaneously influences the interest of entrepreneurship activities. Based on the result of adjusted R square, there are 63.5% simultaneously influence of entrepreneurship lecture and self-motivation toward the entrepreneurship interest. Key Words: entrepreneurship lecture, self-motivation, entrepreneurship interest